QSAR Analysis of 6-Fluoro-3-(4H- 1,2,4-triazol-3-yl)quinolin-4(1H)-ones as Antileukemic Agents using Physicochemical and Alignment Independent Topological Based Descriptors - Wang, Yan; Zhou, Qin; Wang, Li; Ma, Jun-Jie (Letters in Organic Chemistry, 2018)
Background: 6-Fluoro-3-(4H-1,2,4-triazol-3-yl)quinolin-4(1H)-ones are potential antileukemic agents. Method: QSAR analysis of a series of previously synthesized 6-fluoro-3-(4H- 1,2,4-triazol-3-yl)quinolin- 4(1H)-ones (tested for their inhibitory activity against blood cancer) as analogues of fluoroquinolone, was performed with the aid of multiple regression analysis. This could facilitate the exploration of features responsible for the selectivity of the antileukemic activity against HL60 (Human promyelocytic leukemia cell line) among this congeneric series. Using random selection method, 25 analogues of the series were selected as training set while 12 analogues of 6-Fluoro-3-(4H-1,2,4-triazol-3-yl)quinolin- 4(1H)-one were taken as test set for current investigation. Inhibitory Concentration (IC50) values were used to build statistical models with the help of physicochemical and topological descriptors. Results: QSAR equations were developed and they worked well for all the predictions. QSAR models were validated by doing cross validation. Conclusion: The derived model has the capability to predict the activity of new compounds as well as it can also quantitatively explain the critical region to be focused in the molecule.
Keywords: triazolylquinolin-4(1H)-one